Karakter Kimia Kompos Dengan Dekomposer Mikroorganisme Lokal Asal Limbah Sayuran - Nurul Puspita Palupi (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2015)
Organic wastes in Samarinda, East Kalimantan are about 450 tons a day. More than 60 % as a vegetables waste. Refer to the literature, nutrients which contain on the vegetables waste are about 100 ton per waste’s dry weight so it is potential to be an organic fertilizers. The advantages of the organic fertilizer are coping nutrient deficiencies, relieves nutrients fastly, contain complete micro and macro, repairing soil structure then soil become loose, high water holding capacity, and occasionally give the disease resistancy to the plant, and increasing soil microorganism activity. That the reason why organic fertilizer like compost being the alternative for repairing soil degradation. That research aims are to identify the compost quality from the vegetables local microorganism which produces by adding the vegetables with sugar and coconut water. And then that local microorganism was used as the empty bunch palm oil scrabs decomposter. This research told that the compost from the vegetables wastes with local microorganism application held the higher total N, P, K than control.